Gelombang Ideologi Islam Transnasional dalam Sekolah Islam Terpadu - Siregar, Herianda Dwi Putra (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. The development of Integrated Islamic schools is in line with the increasing symptoms of religious conservatism whose roots can be found from tarbiyah movements on public campuses, such as UGM, UI, ITB. In general, Integrated Islamic individuals or groups present themselves with an Islamic identity by returning to